SUPERVISI FORMATIF TERHADAP PENINGKATAN KUALITAS PEMBELAJARAN DI MADRASAH TSANAWIYAH NEGERI 1 ACEH UTARA - Jarniati, Jarniati; Yusrianti, Susi (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The improvement of teaching and learning quality at Madrasah Tsanawiyah Negeri 1 Aceh Utara is an urgent need to strengthen the Islamic education system. In this context, the implementation of formative supervision strategy becomes the main focus in enhancing the effectiveness of learning. This research aims to analyze the impact of implementing formative supervision strategy on the quality of teaching and learning at the madrasah. The research method used is qualitative research with a case study approach. Data were obtained through classroom observations, interviews with teachers and educational staff, as well as analysis of curriculum-related documents and learning evaluations. The results show that formative supervision is effective in improving the quality of teaching and learning at Madrasah Tsanawiyah Negeri 1 Aceh Utara. With formative supervision, teachers can receive constructive feedback, support in competency development, and enhance student engagement in the learning process. However, this research also identifies several challenges faced in implementing formative supervision, including the availability of adequate resources and managerial support. Therefore, recommendations are provided to enhance teacher training in formative supervision, improve collaboration between management and educational staff, and strengthen educational infrastructure to support sustainable implementation